Implementasi pendidikan multikurtural melalui pendekatan nilai luhur budaya dan pancasila untuk membangun karakter mahasiswa dalam meghadapi arus globalisasi - Muhammad Misbahudholam A.R. (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
Globalization is indeed very strongly felt in every aspects of life of society, nation and state. The joints are ediologi, political, economic, social, cultural, defense and security. The fade of nationalism and solidarity is one of the diseases that are suffered by children of this country. This factor is also the background for the emergence of awareness of the importance of education implementation multikurtural in building character/good manners. Characters based on a multicultural nation in accordance with the motto "Bhineka Tunggal Ika/Unity in Diversity" should be the foundation in the development of the character / character the future of the nation of Indonesia. The purpose of this research are: (1) knowing how to approach memalui implementation of multicultural education and cultural values of Pancasila to build student character in meghadapi globalization in STKIP PGRI Sumenep; (2) determine the factors supporting and implementing multicultural education memalui approach and the cultural values of Pancasila in STKIP PGRI Sumenep. This research is a case study with research subjects covering STKIP PGRI Sumenep, chairman, faculty, and students. The approach used is a qualitative approach with descriptive analysis method. The results of this study are: (1) to implement multicultural education through the approach of cultural values and Pancasila run very and able to build student character STKIP PGRI Sumenep (2) factors pendukunggnya is good cooperation between all the components in STKIP PGRI Sumenep, starting from the chairman, lecturers, students and parents of students. Their breadth to students in developing their potential through both intra and extra school.Keywords: Multicultural Education, Student Character. http://dx.doi.org/10.17977/um022v1i22016p089